Penerapan Teknologi Deep Learning dalam Model Pembelajaran Adaptif Menggunakan Smart Learning Bagi Siswa Berkebutuhan Khusus di SMK -PPI Bandung - Andriana; Hidayat, Asep; Zulkarnaen; Dhanureksa, Prima; Farthurrozi, Raedy (Jurnal Pengabdian Tri Bhakti, 2025)
This community service program focuses on ensuring equal access to education for SBK through the use of advanced technology. The methodology begins with identifying the specific needs of SBK through observation and interviews to understand the challenges they face, followed by collaboration with the school and technology developers to design suitable solutions. Intensive training on Deep Learning (DL) technology and inclusive teaching strategies is provided to SMK-PPI teachers, introducing concepts such as Natural Language Processing (NLP), Generative Pre-trained Transformers (GPT), and image processing to support the learning process. The DL-based learning model is then implemented in classrooms involving SBK, with a focus on personalized learning content and more inclusive teaching methods. Continuous evaluation through data collection from observations, interviews, and surveys demonstrates improvements in student engagement, material accessibility, and learning outcomes for SBK. Based on feedback from both teachers and students, reflections and adjustments are made to ensure the sustainability of this model at SMK-PPI and its potential replication in other schools. This program is expected to make a significant contribution to strengthening inclusive education at SMK-PPI Bandung, ensuring that all students have an equal opportunity to reach their full potential.